The Effect of Quality of Work Life and Emotional Intelligence on Performance as Variable Oganizational Commitment through Mediation - Widayanti, Wika; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2019)
The purpose of this study was to determine the effect of the quality of working life and emotional intelligence on the performance through organizational commitment as a mediating variable. The population of this study on nurses at Christian Hospital Ngesti Waluyo Temanggung as many as 189 people. Methods of data collection using questionnaires, interviews, and literature study. The sampling technique using proportional cluster sampling technique as many as 129 people. Methods of data analysis using classical assumption test, regression analysis and path analysis. Data were analyzed using IBM SPSS Statistics 21. The results showed that the quality of work life had a positive effect on organizational commitment. Emotional intelligence positive effect on organizational commitment. Quality of work life has a positive effect on performance. Emotional intelligence has a positive effect on performance. Organizational commitment has a positive effect on performance. The quality of work life positive effect on performance through organizational commitment. Emotional intelligence positive effect on performance through organizational commitment. Suggestions for the agency is to perform the briefing prior to the work and to supervise and control the tasks and responsibilities of the nurse, then evaluated and the results communicated to the person concerned.